Towards a general theory of access - David M Levinson; Hao Wu (Journal of Transport and Land Use)
This paper integrates and extends many of the concepts of accessibility deriving from Hansen’s (1959) seminal paper, and develops a theory of access that generalizes from the particular measures of access that have become increasingly common. Access is now measured for a particular place by a particular mode for a particular purpose at a particular time in a particular year. General access is derived as a theoretical ideal that would be measured for all places, all modes, all purposes, at all times, over the lifecycle of a project. It is posited that more general access measures better explain spatial location phenomena.